O Lord how long? : a revival movement in New Zealand, 1920-1933 : a thesis in partial fulfilment of the requirements for the degree of Master of Arts with Honours in History at Massey University - Ireton, Douglas E (Massey University, 1986)
New Zealand in the 1920s and early 1930s witnessed the development of a revivalist movement. This was in the context of a New Zealand that faced the future tentatively, in the shadow of the most apocalyptic war of modern times. It was a period of new beginnings, but many of the new beginnings had a familiar ring about them. While the period marked expansion in terms of communication and transport, power generation and land settlement, in the political arena much was reassuringly familiar. The 1920s was a period of economic uncertainty with fluctuations of recession followed by slight recovery. As the decade progressed this uncertainty gradually deteriorated into what is now known as the Depression. Politically, reassurance took a number of forms. W F Massey started the decade with his only overwhelming victory at the polls. The Docembor 1919 election gave his Reform Party 47 seats in an 80 seat Parliament, the rest shared among Liberals, Labour, and Independents. To Massey the Bible and the freehold 'cow cocky' were the twin paths to prosperity. Not for him was the challenge of an independent line. He resisted Dominion status and regarded 'the British Empire as a single undivided unity'. Keith Sinclair, The Pelican History of New Zealand. Revised Edition, Harmondsworth 1980, p 246. He was happy in the safe hands of British Imperialism.
Keywords: New Zealand; Revivals